On Earth as it is in heaven: A study of nineteenth‐century religious communal experiments in the United States. Issue 1 (17th December 2019) - Hart, Amy
Abstract: This article provides an introduction to the scholarship on religious communal experiments in nineteenth‐century United States for scholars and students of history. The author approaches this scholarship from the perspective of a historian, thus primarily exploring historians' scholarship on these communities. In a similar vein, this article highlights historical communities, as opposed to those utopias that remained exclusively within the literary genre. This article first explains the history of communal studies scholarship and its traditional focus on the "big three" communities: Oneida, the Shakers, and the Church of Jesus Christ of Latter‐Day Saints, previously referred to as the Mormons. The article then explores the evolution of the scholarship since the mid‐twentieth century, including the implementation of new historical methodologies and emphases on race and gender in the study of these communities. Finally, this article looks toward the future of communal studies scholarship, anticipating the next direction this scholarship will take.